Macroeconomic Determinants of Indonesia’s Refined Palm Oil Export Perfomance: Evidence from China, India and Pakistan (2010-2024) - Jeisica Jeisica; Niniek Imaningsih (Universitas Pasundan, 2026)
Indonesia is the world’s largest producer and exporter of palm oil, with refined palm oil (RPO) playing an increasingly strategic role in export diversification and downstream industrialization. However, the export performance of Indonesia’s refined palm oil remains volatile, indicating that competitiveness is influenced not only by production capacity but also by macroeconomic conditions, external demand, and international competition. This study examines the determinants of Indonesia’s refined palm oil exports to China, India, and Pakistan during 2010–2024 using a panel data econometric approach. The analysis incorporates the Real Effective Exchange Rate (REER), trading partner GDP, competitor prices, and downstream industrial policy within a unified framework. Model selection tests identify the Common Effect Model (CEM) as the most appropriate specification. The results show that REER has a negative and statistically significant effect on exports, indicating that exchange rate appreciation weakens Indonesia’s export competitiveness. In contrast, trading partner GDP and competitor prices positively and significantly affect refined palm oil exports, reflecting the importance of external demand and substitution effects in global markets. Meanwhile, the downstream industrial policy variable has a positive but statistically insignificant effect. Overall, the findings suggest that Indonesia’s refined palm oil exports are primarily driven by international competitiveness and global market dynamics rather than domestic policy intervention alone.